Issues of urbanization in Malaysia / Nurulhuda Ali ... [et al.] - Ali, Nurulhuda; Alias, Anuar; Che Pin, Siti Fairuz; Othman, Khairul Nizam (2021)
Malaysia is currently one of the most urbanized countries of East Asia, and also one of the most rapidly urbanized regions around the world. The development growth in Malaysia is striving towards developed country. Currently development has encroached towards most urban areas and has filled with property development and causes most of the urban areas highly dense and congested. As population is growing, the demand for residential development in the city center and its surrounding rises. Urbanization is putting pressure on the government to find means to manage its resources. On top of that, it has consequence to other problems related to urbanization such as urban poverty, urban congestion, high crime rates, urban sprawl and lots more issues related to rapid urbanization. Objective of this study is to identify the issues resulted from the rapid urbanization and its impacts towards the growth of economy, social and environment in Malaysia. This study also aims in suggesting how the government should tackle these problems. To obtain the data of this study, Qualitative content analysis is used to derive to the research problems and issues. The outcomes are expected to assist Malaysia in achieving the SGD 11 goals towards sustainable cities and communities.